1989
DOI: 10.2343/geochemj.23.65
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen and carbon isotopic compositions of methane in N2- and CO2-rich gases from Central Japan.

Abstract: N2 and C02-rich bubble gases collected from five springs and four wells in Paleozoic metamorphic rock and Cretaceous granite areas of Central Japan contain up to 22.9% methane. 6D and 613C values are between 100 and -180%o, and between -24 and -51 %o, respectively, for the methane. A linear correlation between 6D and 813C values observed is almost identical with that for the TT(m) type ther mogenic methane. The methane in the bubble gases is likely to be originated by thermal decomposition of organic matter in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 25 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Therefore, it may represent a gas formed by fermentation and/ or thermogenic decomposition of organic materials in sedimentary bedrocks. MIZUTANI et al (1989) suggested that CH 4 is likely to be formed by mixing of thermal decomposition of organic matter in deep-seated sedimentary rocks and biogenic methane, according to the isotopic data of the sample gas methane at the HOS (dD = -178% and d 13 C = -51.1%). produced an irreversible change in the subsurface gas composition year by year.…”
Section: Origins Of Gasmentioning
confidence: 99%
“…Therefore, it may represent a gas formed by fermentation and/ or thermogenic decomposition of organic materials in sedimentary bedrocks. MIZUTANI et al (1989) suggested that CH 4 is likely to be formed by mixing of thermal decomposition of organic matter in deep-seated sedimentary rocks and biogenic methane, according to the isotopic data of the sample gas methane at the HOS (dD = -178% and d 13 C = -51.1%). produced an irreversible change in the subsurface gas composition year by year.…”
Section: Origins Of Gasmentioning
confidence: 99%